Kegiatan Pendampingan Pemasaran Kreatif untuk Meningkatkan Daya Tarik Desa Pekarungan - Mohammad Fikri Akbar Saputra (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Community mutual cooperation activities often give rise to diverse social dynamics. On one hand, there are challenges such as differences in background, individual busyness, and varying levels of community participation. On the other hand, there is a valuable opportunity to strengthen social character through togetherness. Therefore, mutual cooperation plays an important role as a foundation for building a community culture based on strong values of care and solidarity. The main objective of this activity is to analyze and describe the extent to which mutual cooperation can strengthen community cohesion in Pekarungan Village, Sukodono District, as well as to examine the influence of cooperation, care, and responsibility on the improvement of social solidarity. This community service activity (PKM) employs the Participatory Action Research (PAR) method as the primary approach to fostering community togetherness, involving stages such as problem identification, participatory planning, implementation of mutual cooperation activities, mentoring, and evaluation through collective reflection. In this approach, the community is actively involved as subjects in every stage of the activity. The results indicate a significant increase in community participation in mutual cooperation activities, along with a notable improvement in social awareness. The interactions established during the activities help strengthen social relationships and create a more harmonious environment. Therefore, this mutual cooperation activity makes a tangible contribution to enhancing togetherness and improving the quality of social relationships within the community of Pekarungan Village, Sukodono District.